Fabrication of an interim buccal-retaining flange obturator for a patient undergoing partial maxillectomy - Radhwan Algabri; Sadeq Altayyar; Ahmed Yaseen Alqutaibi; Hanan Aboalrejal; Abdalhaq Alhasani (Wolters Kluwer Medknow Publications, 2024)
Prosthodontic treatment of palatal defects focuses on closing oronasal communication and improving masticatory function, speech, esthetics, and comfort. The most difficult aspect of rehabilitating patients with hemimaxillectomy is ensuring the prosthesis has enough retention and stability. During healing, a simpler design and effective retention should adequately meet the patient's functional requirements. This case report presents the fabrication of an interim cost-effective and retentive buccal flange palatal obturator for a 65-year-old male patient who had an acquired maxillary defect resulting in mastication and deglutition difficulties. In this report, the retention of the obturator was achieved by utilizing the remaining teeth and employing a flexible thermoplastic buccal flange, with a wrought-wire U-shaped loop, on the buccal surfaces of the left canine, premolars, and molars. A complete palatal acrylic palate was designed to achieve optimal distribution of load to the surrounding tissues. To enhance patient comfort, the obturator featured a closed hollow bulb, reducing its overall bulk and making it lightweight. This interim prosthesis successfully rehabilitated the patient, resulting in improved masticatory efficiency, enhanced speech clarity, and an overall improvement in the patient's quality of life.